Chinese burden of depressive disorders from 1990 to 2021 and prediction for 2030: analysis of data from the global burden of disease study 2021 - Na Yan; Caochen Zhang; Yihan Wang; Yuhao Wang; Yunjiao Luo; Yingxue Wang; Blen Dereje Shiferaw; Louisa Esi Mackay; Jingjing Wang; Jie Tang; Qingzhi Wang; Xiuyin Gao; et al. (BMC Psychology)
Abstract Background This study aims to examine the temporal changes in the incidence, prevalence, and disability-adjusted life years (DALYs) of depressive disorders as well as its association with age, period, and birth cohort among Chinese from 1990 to 2021, and forecast the future trends of incidence rates and numbers from 2022 to 2030. Methods Data for analysis were obtained from the Global Burden of Disease (GBD) 2021. Joinpoint analysis was used to calculate the annual percentage change (APC) and average annual percent change (AAPC) to describe the rates of depressive disorders. Age, period, and cohort model was utilized to disentangle age, period, and birth cohort effects on rates of depressive disorders. Bayesian age-period-cohort (BAPC) analysis was capitalized to forecast the incidence rates and numbers for different sexes and age groups from 2022 to 2030. Results The age-standardized incidence (ASIR, AAPC: -0.35 [95%CI: -0.65, -0.04]), prevalence (ASPR, AAPC: -0.20 [95%CI: -0.24, -0.16]), and DAYLs (AAPC: -0.28 [95%CI: -0.51, -0.05]) rates of both sexes showed a downward trend from 1990 to 2021, despite a volatility growth in recent years (APC in 2019–2021 of ASPR: 0.96 [95%CI: 0.70, 1.23]). Females exhibited a higher burden of depressive disorders compared to males but experienced a more rapid rate of reduction changes. The burden of depressive disorders was most owing to the age effect and period effect in recent years. The ASIR was predicted to decrease in the whole population (males in 2030: 1,546.3 per 100,000 people; females in 2030: 2,465.8 per 100,000 people), but in children, adolescents, and the elderly demonstrate unfavorable trends in the future. Conclusion The burden of depressive disorders decreased in China from 1990 to 2021 in terms of age-standardized rates, but increased in recent years. Children, adolescents, and the elderly are the risk groups for future depressive disorders. Considering the large population, the increasing fewer children, and the aging trend, as well as the possible long-term effects of COVID-19 on human psychological burden, more sex-age-sensitive social healthcare programs should be considered in the future to minimize the burden of depressive disorders in China.